2017
DOI: 10.1097/fjc.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Novel Oral P2Y12 Receptor Inhibitors in Patients With ST-Segment Elevation Myocardial Infarction Undergoing PCI: A Systematic Review and Meta-Analysis

Abstract: Abstract:The efficacy and safety of novel oral P2Y12 receptor inhibitors (prasugrel and ticagrelor) are subjects of contention in patients with ST-segment elevation myocardial infarction (STEMI) undergoing PCI, and the optimal duration of therapy remains uncertain. We searched PubMed, Embase, Cochrane Library, CNKI, VIP, and WanFang Data to identify randomized controlled trials comparing novel oral P2Y12 receptor inhibitors with clopidogrel in patients with STEMI undergoing PCI until February 2016. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
4
3
0
Order By: Relevance
“…A recent meta-analysis of nine DAPT trials indicated that patients taking ticagrelor had lower rates of adverse events (OR = 0.88; 95% CI, 0.81–0.95) [26]. This is consistent with our finding that T-DAPT patients had less MACE (10.9% vs. 18%, p = 0.003) and reduced all-cause mortality (HR = 0.48; p = 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…A recent meta-analysis of nine DAPT trials indicated that patients taking ticagrelor had lower rates of adverse events (OR = 0.88; 95% CI, 0.81–0.95) [26]. This is consistent with our finding that T-DAPT patients had less MACE (10.9% vs. 18%, p = 0.003) and reduced all-cause mortality (HR = 0.48; p = 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…According to the type of therapy, the risk of gastrointestinal bleeding did not differ between clopidogrel-based DAPT and new antiplatelet-based DAPT group. These results support the conclusions of some studies [16][17][18][19][20][21][22] but differ from others [9][10][11][12][13][14][15]; however, the designs are not comparable. First, most studies have analyzed bleeding as a secondary endpoint and determined the overall risk of bleeding (including, e.g., epistaxis, intracranial, and hematuria) and not specifically gastrointestinal events.…”
Section: Discussionsupporting
confidence: 46%
“…Similarly, in the Study of platelet inhibition and patient outcomes (PLATO trial) [10], compared with the clopidogrel group, the ticagrelor group had a higher risk of major bleeding that was not related to coronary artery bypass graft. However, subsequent studies have yielded contradictory results, with an increased risk of bleeding with prasugrel and ticagrelor in some of them [9][10][11][12][13][14][15], but no differences between clopidogrel and these new compounds in others [16][17][18][19][20][21][22]. The main limitation of acquiring meaningful comparisons among studies and these antiplatelet agents is the variability in bleeding definitions used [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with non-ST segment elevation acute coronary syndrome, results of a subsequent meta-analysis of 4 RCTs indicated that a novel P2Y 12 antiplatelet was associated with a significantly reduced rate of MACE compared with clopidogrel (risk ratio [RR] = 0.87), but the incidences of major and minor bleeding events were significantly higher (RR = 1.27, 1.20) [14]. For patients with STEMI, results of 3 meta-analyses of RCTs consistently indicated that prasugrel and ticagrelor were more efficacious than clopidogrel for reducing the risk of MACE, although the rates of bleeding events were similar [15][16][17].…”
Section: Discussionmentioning
confidence: 99%